Study the Content of some Secondary Metabolites in Roots of Glycyrrhiza glabra Gathered from Different Natural Localities in Kerman Province of IRAN - H Oloumi (Journal of Medicinal Plants, 2012)
Background: Glycyrrhiza glabra roots and rhizomes which are extensively used in herbal medicines for them health effects containing more than 100 various useful compounds including phenolics and triterpene saponins (glycyrrizin) grow as a weedy plants in many different localities of Kerman province.